Component structure of the educational complex of Chernigiv region - Ryabokon, Olena (Human Geography Journal, 2017)
In the article the component structure of the educational complex is defined, its main structural units are analyzed. Established what factors influence the placement of heterogeneous schools in Chernihiv region The dynamic of the educational establishments of the region and inter-regional differences of their distribution are defined. Now, research educational complex deals with many scientists. Actually geographers study conducted diverse educational complex at different levels, namely national, regional. Also, studies of functional components and complex relationships that are formed as a result of functional and components. Scientists are trying to make every effort to improve the operation of the educational sector and develop appropriate programs that also contribute to the improvement of the educational complex whole.After analyzing the component structure of the educational complex of Chernihiv region we can make the following conclusions: Firstly: the heterogeneous distribution of educational institutions in theterritoryofChernihivregion is affected by a number of demographic, settlement and socio-economic factors. Secondly, for the full existence of the educational complex all its structural components must operate in full force. Each component becomes important. So when the reforms in the education sector take place, it should be taken into account that a change of one structural component will lead to the changes of other structural components of the educational complex.Thirdly, only coordinated work of state and local government of educational complex will function properly.